2009
DOI: 10.1007/s00038-009-0085-z
|View full text |Cite
|
Sign up to set email alerts
|

Examining the association between socioeconomic position and body mass index in 1978 and 2005 among Canadian working-age women and men

Abstract: The SEP-BMI association in Canada is complex, showing variation by gender, by aspect of SEP, across the BMI distribution, and at different time points. The association departs from the more consistent social gradient in health, thereby challenging our view of BMI as a typical health issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
(22 reference statements)
3
10
3
Order By: Relevance
“…In women, higher income adequacy levels were weakly associated with lower BMI. These findings agree with those established in the literature: higher income is associated with increased obesity risk in men but decreased risk in women [30,32,33,35].…”
Section: Relationship Between Diet Quality and Adult Obesitysupporting
confidence: 94%
See 1 more Smart Citation
“…In women, higher income adequacy levels were weakly associated with lower BMI. These findings agree with those established in the literature: higher income is associated with increased obesity risk in men but decreased risk in women [30,32,33,35].…”
Section: Relationship Between Diet Quality and Adult Obesitysupporting
confidence: 94%
“…Respondents' education status was not statistically significant, which is contrary to many studies showing an inverse association between education and BMI [32,35,26].…”
Section: Relationship Between Diet Quality and Adult Obesitycontrasting
confidence: 80%
“…However, we discover the significant relationships between sleep duration and BMI in certain BMI percentiles by using quantile regression to account for the potential heterogeneous effect of sleep duration. Similarly, previous studies that utilize quantile regression are also able to reveal significant relationships between various covariates and BMI in certain quantiles when OLS models show insignificant results (McLaren et al 2010;Shankar 2010). Our results highlight the importance of examining the effects of covariates across the entire distribution of BMI.…”
Section: Discussionmentioning
confidence: 62%
“…Thus, the different impact of the same covariate on the higher or lower tails of BMI distribution may be revealed. Several studies have shown that quantile regression can provide more information than OLS in exploring the effects of various socio-economic factors on BMI (McLaren et al 2010;Shankar 2010;Stifel and Averett 2009).…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation